2022
DOI: 10.3389/fpsyg.2022.996962
|View full text |Cite
|
Sign up to set email alerts
|

How organizational trust impacts organizational citizenship behavior: Organizational identification and employee loyalty as mediators

Abstract: Research on the influence of organizational trust (OT) on organizational citizenship behavior (OCB) of employees has been conducted for years, but the influence of internal mechanism for OT on OCB is not well studied. Based on social exchange theory and organizational identity theory, this paper explored the OT on the OCB and revealed the chain-mediating role of organizational identification (OI) and employee loyalty (EL) from both employees’ cognitive and psychological perspectives. The research employed a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…The motivation dimension comprised 8 questions, each evaluated on a five-point Likert scale ranging from strongly disagree [ 1 ] to strongly agree [ 5 ], resulting in a score range of 8–40. The attitude dimension consisted of 22 questions, evaluated on a five-point Likert scale with scores ranging from strongly disagree [ 1 ] to strongly agree [ 5 ], yielding a score range of 22–110. The practice dimension featured 11 questions, evaluated on a five-point Likert scale with response options ranging from always [ 5 ] to never [ 1 ], and scores ranging from 11 to 55.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation dimension comprised 8 questions, each evaluated on a five-point Likert scale ranging from strongly disagree [ 1 ] to strongly agree [ 5 ], resulting in a score range of 8–40. The attitude dimension consisted of 22 questions, evaluated on a five-point Likert scale with scores ranging from strongly disagree [ 1 ] to strongly agree [ 5 ], yielding a score range of 22–110. The practice dimension featured 11 questions, evaluated on a five-point Likert scale with response options ranging from always [ 5 ] to never [ 1 ], and scores ranging from 11 to 55.…”
Section: Methodsmentioning
confidence: 99%
“…The attitude dimension consisted of 22 questions, evaluated on a five-point Likert scale with scores ranging from strongly disagree [ 1 ] to strongly agree [ 5 ], yielding a score range of 22–110. The practice dimension featured 11 questions, evaluated on a five-point Likert scale with response options ranging from always [ 5 ] to never [ 1 ], and scores ranging from 11 to 55. Notably, three practice questions were open-ended and not assigned numerical scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They pointed out employee trust as a critical determinant of employee work commitment and organizational loyalty. Moreover, the literature revealed by Dai et al [ 51 ] concluded that trust builds strong psychological attachments and guides employee work behavior toward organizational loyalty. In the context of business sectors, empirical research confirmed the impact of employee trust on a number of positive outcomes in different corporate sectors.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Helliwell and Huang [ 52 ] found that employee trust enhances job satisfaction, well-being, and innovative work behavior [ 49 ]. According to the social exchange theory, employees’ work behaviors and attitudes are influenced by the level of trust they perceive in the organization [ 51 ]. In addition, Kim and Park [ 53 ] noted that trust shapes employees’ attitudes and behaviors in the workplace.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%